Answer:
Let B = the brothers age now
Let L = Lisa's age now
Then today:
L = 7B
And three years from now, Lisa's current age plus 3 equals 4 times the brothers age plus 3 represented by the following formula
L+3 = 4(B+3)
Now we can substitute the value of L in the first formula for L in the second formula
7B + 3 = 4(B+3)
So the answer is C
Step-by-step explanation:
1.(first second or third)
2.( first second or third)
3.(first second or third)
Step-by-step explanation:
1.(first second or third)
about 1.77 seconds
about 6 seconds
about 25 seconds
B.) about 1.77 seconds